1992
DOI: 10.1111/j.1365-3040.1992.tb00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of freezing tolerance and vernalization responses in Cruciferae exposed to a low temperature

Abstract: High levels of freezing tolerance were induced in leaves of different Cruciferae species including Brassica napus, Arabidopsis thaliana, Barbarea vulgaris, Thlaspi arvenses and Descurainia sophia by low‐temperature acclimation. Concomitantly, the amount of total RNA doubled in these three species. Analyses of methylation patterns and dosage of rRNA genes were carried out to determine whether or not alterations occur in this DNA during development of freezing tolerance. Hybridizations of Southern transfers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
(22 reference statements)
0
20
0
Order By: Relevance
“…4). Leaves from all three species are capable of developing frost tolerance after cold acclimation (Gilmour et al, 1988;Laroche et al, 1992). Neither the cold-1 2 3 4 5 6 7 8 -20°C----2°C --- Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4). Leaves from all three species are capable of developing frost tolerance after cold acclimation (Gilmour et al, 1988;Laroche et al, 1992). Neither the cold-1 2 3 4 5 6 7 8 -20°C----2°C --- Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…A strong hybridization signal to pBN115 was also observed for RNA isolated from leaves of D. sophia (flixweed) acclimated at 2°C. Flixweed cold acclimates more quickly and is capable of developing a higher degree of freezing tolerance than any other crucifer tested (Laroche et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the transcript levels for Phe ammonia lyase and chalcone synthase increase 10-fold in Arabidopsis thaliana in response to low temperature (Leyva et al, 1991). Laroche et al (1992) suggested that amplification and differential methylation of rDNA may be related to vernalization rather than freezing tolerance. Although there are reports that exposure of chilling-sensitive plants to low temperatures alters gene expression (Hahn and Walbot, 1989;Christie et al, 1991;Christie and Walbot, 1991), these responses may be pathological symptoms of stress rather than adaptive responses.…”
mentioning
confidence: 99%
“…Amplification of satellite DNA was demonstrated in orchid in response to hormones, 6 in Vicia faba during de-differentiation of root cells, 7 and in tobacco in response to wounding or tobacco mosaic virus infection. 8 Changes in rDNA copy number were seen in Brassica napus and Descurainia sophia during low temperature acclimation, 9 and variability in DNA content influenced by light quality and quantity was demonstrated in sunflowers. 10,11 Therefore, the understanding of the control of the genomic changes that take place in flax has the potential to be applied to similar changes that take place in a wide variety of plants.…”
mentioning
confidence: 99%